2018
DOI: 10.1097/lgt.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Spray Versus Paracervical Block During Loop Electrosurgical Excision Procedure: A Randomized Trial

Abstract: The local 40 mg of 10% LS can be used to substitute for PB for pain control during LEEP of the cervix. It also resulted in fewer adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…Despite the fact that a LEEP is a brief procedure, it can cause significant pain and discomfort to the patient. On average, a visual analogue score (VAS) of 4 points was reported due to electrical excision during the procedure even with local anesthesia [14,15]. The cervix is a small procedural target and located deep inside the vagina.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that a LEEP is a brief procedure, it can cause significant pain and discomfort to the patient. On average, a visual analogue score (VAS) of 4 points was reported due to electrical excision during the procedure even with local anesthesia [14,15]. The cervix is a small procedural target and located deep inside the vagina.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference between the two groups for the mean volume of the excised tissue for LA 1.02 (0.2-1.8) cm 3 versus GA 1.125 (0.9-1.5) cm 3 , surgery time including LA application and GA induction and emergence 23.5 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Serious complications from the different forms of anaesthesia did not occur. Postoperative vomiting occurred three times in the GA group, and brief tachycardia occurred once in the LA group.…”
Section: Further Resultsmentioning
confidence: 92%
“…However, in another study, the use of lidocaine in the form of a spray was compared with paracervical block during loop electrosurgical excision procedure, and it was reported that LS could be used instead of paracervical block for pain management [29].…”
Section: Discussionmentioning
confidence: 99%